Metal/polymer composite material and method for fabricating the same - HSIAO, WEI-TIEN; LAI, HONG-JEN; CHEN, TAI-SHENG; LEU, MING-SHENG (2016)
A metal/polymer composite material is disclosed, wherein the metal/polymer composite material comprises a polymer layer and a metal heat-dissipation layer. The heat-dissipation layer comprises a roughed surface with an isotropic surface roughness. The metal heat-dissipation conformally blankets over the roughed surface.